Golden Perception: Simulating Perceptual Habits of the Past. (September 2013) - Carbon, Claus-Christian; Deininger, Pia
Medieval times were neither dark nor grey; natural light illuminated colourful scenes depicted in paintings through coloured windows and via artificial beeswax candlelight. When we enter, for example, a church to inspect its historic treasures ranging from mosaics to depictions of saints, we do this under quite unfavourable conditions; particularly as we mainly depend on artificial halogen, LED or fluorescent light for illuminating the desired object. As these light spectrums are different from the natural light conditions under which the old masterpieces were previously developed and perceived, the perceptual effects may dramatically differ, leading to significantly altered affective and cognitive processing. Different qualities of processing might particularly be triggered when perceiving artworks which deal with specific material prone to strong interaction with idiosyncratic light conditions, for instance gold-leafed surfaces that literally start to glow when lit by candles. We tested the perceptual experiences of a figurative piece of art which we created in 3 (foreground) by 3 (background) versions, illuminated under three different light conditions (daylight, coloured light and beeswax candlelight). Results demonstrated very different perceptual experiences with stunning effects for the interaction of the specific painting depicted on a gold-leafed background lit by candlelight.